Improving MSMEs' Networking through Digital Marketing: The Role of Copywriting - Bima Cinintya Pratama; Maulida Nurul Innayah; Miftahul Furqon (PT FORMOSA CENDEKIA GLOBAL, 2023)
In today's digital era, digital marketing is one of the keys to business success. One of the applications of digital marketing is copywriting techniques. This community service activity aims to increase knowledge, understanding, and implementation of information technology for digital marketing activities for MSMEs in Banyumas Regency. From preliminary interviews with MSME managing partners, several main problems were identified in marketing their business, including understanding digital marketing, techniques to increase online sales and product reputation. According to the needs of these participants, this activity explains digital marketing. In addition, this community service activity also emphasizes the importance of using English in digital marketing. The stages of implementing Community Service are providing knowledge about digital marketing, understanding copywriting, and practicing making English copywriting. This activity uses lecture methods, tutorials, discussions, and practices through Aisyiyah Entrepreneurial School activities. The activity results are evaluated through questions and answers with participants. The results of this activity are expected to show that MSME participants have started to apply English copywriting techniques to run their businesses.